Navajo Places - Linford, Laurance D. (Book collections on Project MUSE., 2000)
A place-name guide covering the entire traditional Navajo homeland includes some 1,200 entries appearing in alphabetical order by name and organized by state. Each entry includes the English name, elevation, county, meaning of the Navajo name, significance if known, description, and location. Also includes introductory material outlining Navajo history, culture, and ceremony.